Implementasi program pembinaan kebugaran jamaah haji berbasis latihan terstruktur di Kota Semarang - Siti Baitul Mukarromah; Sahri Sahri; Gustiana Mega Anggita; Rikha Liemiyah (CV Rezki Media, 2025)
The majority of Hajj pilgrims in Semarang City are over 50 years old and have varying levels of physical fitness, with little to no structured physical activity prior to departure. This condition increases the risk of fatigue and musculoskeletal complaints and reduces physical readiness for performing the Hajj rituals. To address these needs, the service team implemented a structured exercise-based fitness training program tailored to the pilgrims' conditions. The program was conducted over eight weeks, with three training sessions per week, covering light to moderate intensity aerobic exercises, muscle strengthening, flexibility, and healthy lifestyle education related to nutrition, rest, and stress management. The methods and results of the activities were carried out in Semarang City, involving 75 pilgrims registered for the 2025 Hajj season. The program was implemented using a planned exercise method over eight weeks, with a frequency of three times a week, incorporating light to moderate intensity aerobic exercises, muscle strengthening to increase endurance, flexibility exercises, and healthy lifestyle education on diet, rest, and stress management. Evaluation was conducted through cardiorespiratory fitness tests (6-minute walk test), leg muscle strength measurements, and body mass index. The results of the program showed a significant improvement in the participants' fitness, marked by an increase in the 6MWT distance from 420.3 ± 52.1 meters to 510.7 ± 47.6 meters (p < 0.05), an 18.4% increase in leg muscle strength, and a decrease in average BMI of 0.9 kg/m². Participants also reported an improvement in motivation and a deeper understanding of the importance of physical preparation. This program has proven to be effective and can be recommended as a fitness training strategy for Hajj pilgrims.